SWOT ANALYSIS IN DETERMINING UMRAH WORSHIP SERVICE STRATEGY AT PT. DARUL ARQAM - Putriani, Erin Nur; Rahayu, Wicha Dewi; Kamila, Inayah Rahma (Institut Agama Islam Negeri Metro, 2025)
This study employs a SWOT analysis to evaluate the strategic positioning of PT. Darul Arqam, an Umrah travel agency operating since June 2023 in Kraksaan, Probolinggo. Utilizing a qualitative descriptive approach, primary data were gathered through in-depth interviews, field observations, and internal documentation. Key findings highlight strengths in quality manasik guidance, adequate facilities, and responsive management, while weaknesses include limited operational scale and product diversification. Opportunities arise from growing demand for Umrah plus halal tourism and airline partnerships, countered by threats from industry competition, regulatory changes, and price fluctuations. The SWOT matrix and Cartesian diagram inform four strategies: SO (expanding Umrah plus tour packages), WO (enhancing human resources and digital promotion), ST (improving operational procedures for regulatory compliance), and WT (strengthening internal efficiency and service diversification). These findings offer actionable recommendations to enhance PT. Darul Arqam’s competitiveness and service quality.